Chemical Composition of Essential Oil from Fresh Salvia Rosmarinus from Jordan at Different Drying Methods - Al-Ghoul, Areej M.; Alwardat, Sara; Abdelhalim, Abeer R. (International Journal of Membrane Science and Technology, 2023)
The composition of essential oil is affected by different drying methods. The present study aimed to evaluate the effect of drying methods (shade-drying (SD), oven-drying(OD), and freeze-drying (FD)) on the essential oils composition of Salvia rosmarinusat. The extracted S. rosmarinusessential oil samples subjected to different drying methods were extracted by hydrodistillation and analyzed by gas chromatography-mass spectrometry (GC-MS). Eighty-three compounds were tentatively identified, with 1,8-cineole, ?-pinene, ?-fenchene, and bornyl being the major components. The shade-dried method best maintained the composition of rosemary essential oil and showed the best retention of ?-Pinene, 1,8-Cineole, the most important compounds, as well as ?-terpineol and safranal. The oven-dried method displayed the worst results, with a significant loss of 37 compounds. However, oven-drying produces a significant increase in the concentrations of borneol, iso-menthol, ?-terpineol, camphor, and bornyl acetate.